A new framework for fiscal policy consolidation in Europe - Peter Bofinger; Stefan Ried (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2010)
Current developments in Greece make clear that the rules of the European Stability and Growth Pact (SGP) were neither strict enough nor enforced strictly enough. To deal with the ongoing fiscal exit and its related phenomena of crisis, we propose a new framework for fiscal policy consolidation in Europe. Centre stage takes a European Consolidation Pact (ECP) supplementing the SGP, with five distinguishing features. First, members are obliged to detail a path to balancing their budgets, including a concrete course to cutting non-cyclical government expenditure, and second to implement an automatic tax increase law in case of straying from the defined path. Third, pact members may apply for ECP guarantees for each newly issued government debt that is in line with the specified path. These guarantees are, fourth, paid for by a percentage fee. Fifth, non-compliance with the automatic tax increase law or voluntary exit from the consolidation pact leaves future government bond issues without ECP guarantees: either the country does not need the guarantee any longer, or it is willing to default. In the latter case, the new framework spells out the details of an orderly government default.
Keywords: E6; F5; H6; 330; Stability and Growth Pact; European Consolidation Pact; Sovereign Default; European Monetary Fund